Spatiotemporal variation characteristics and system dynamic simulation of China’s marine fishery carbon emissions - TIAN Peng, WANG Haohan, LI Jialin, LIU Yongchao, ZHANG Haitao, ZHONG Jie, GONG Hongbo (Ziyuan Kexue, 2023)
[Objective] Accurately assessing the carbon emissions of marine fisheries and predicting its future development trend will help promote energy conservation and emission reduction in China’s marine fisheries, accelerate the realization of the goal of “carbon neutrality”, and promote the sustainable development of China’s marine fisheries. [Methods] Based on the economic data of China’s marine fisheries from 2006 to 2020, this study used the data of mariculture, marine fishing and seafood processing tocomprehensively calculated the carbon emissions of marine fisheries, revealed the driving factors of carbon emissions of marine fisheries with the Log Mean Divisia Index (LMDI), and combined with the system dynamics model to simulate the trend of change of marine fishery carbon emissions under different scenarios in the future. [Results] The results show that: (1) From 2006 to 2020, China’s marine fishery carbon emissions decreased by 653500 tons. The carbon source was dominated by marine fishing and tended to decline, while the carbon sink was dominated by shellfish and grew rapidly. High-value areas of carbon emissions and carbon sources were concentrated in Zhejiang Province, and high-value areas of carbon sinks were concentrated in Shandong and Fujian Provinces. The center of gravity of China’s marine fishery carbon sources, carbon sinks, and carbon emissions moved to the northwest, northeast, and southwest, respectively. (2) The driving effects of carbon sinks and carbon emission coefficient, energy intensity, and industrial structure improvement weakened the total carbon emissions of marine fisheries, while the effects of increasing industrial scale and employed population exacerbated the growth of carbon emissions of marine fisheries. (3) The carbon emissions of marine fishery in the future all show a potential increasing trend, with the characteristics of rapid economic development scenario > current utilization level scenario > energy efficiency adjustment scenario > carbon sink enhancement development scenario > industrial structure adjustment scenario. [Conclusion] Studies have shown that China’s future marine fisheries carbon reduction efforts still face significant challenges. In order to promote energy-saving, emissions reduction, and high-quality development of China's marine fisheries, it is necessary to accelerate the adjustment and upgrading of the industrial structure, increase investment in marine fisheries technology, and actively develop carbon sequestration fisheries and recreational fisheries.